7th Earoph congress : human settlements in the development process, 9-15 March, 1980, Regent of Kuala Lumpur, Kuala Lumpur, Malaysia : keynote addresses - Earoph Congress (7th : 1980 : Kuala Lumpur, Malaysia) 595931 (Kuala Lumpur : The Malaysian Organisation for Human Settlements, 1980)
PSZJBL